Aortic Atherosclerosis: An Updated Review of Current Guidelines and Management Approach—A Literature Review - Mubder, Mohamad; Dugal, Jasmine; Houshmand, Nazanin; Tak, Tahir (International Journal of Angiology, 2025)
Aortic atheroma (AA) is defined by the development of atherosclerotic plaques within the aorta wall and is associated with unfavorable cardiovascular outcomes such as cryptogenic stroke, systemic embolism, and other major adverse cardiac events (MACE). The clinical significance of AA is discussed in this review along with its relationship to cardiovascular outcomes. The purpose of this review article is to present a thorough summary of the current state of knowledge on AA, including its pathogenesis, classifications and grading systems, clinical implications, methods for diagnosis and imaging, therapeutic modalities and treatments, and lastly pertinent complications. There are various methods of AA classification or grading, which entail scoring extent of disease via plaque thickness, severity of atherosclerosis, or by the presence of mobile components or ulcerations. The implications of AA as a systemic atherosclerotic process on the development of coronary artery disease and MACE include, but are not limited to, vascular diseases such as strokes or peripheral arterial disease. The diagnostic approaches include multiple invasive and noninvasive imaging modalities. The treatment strategies range from prevention to medical therapy to invasive surgical interventions. The present evaluation highlights the significance of sustained investigation and advancement in the domain of aortic atherosclerosis to augment precision in diagnosis and effectiveness of treatment.
Keywords: atherosclerosis; aortic plaque; cardiovascular disease; aortic calcification; intimal thickening; plaque rupture; transthoracic echocardiogram; imaging aorta